Molecular mechanism of DdSOC1 gene regulating flower bud initiation in Diospyros deyangensis - WAN Jianqi; DING Yu; REN Han; LI Wenxia; YANG Yong; HUANG Jinmeng; GUAN Changfei (Guoshu xuebao)
[Objective] Seedlings of the new identified persimmon species Diospyros deyangensis have a short juvenile stage and can flower within one year after seed sowing. The function of the DdSOC1 gene in controlling flower bud initiation in D. deyangensis was investigated, along with its sequence characterization and expression pattern. [Methods] Plant materials were obtained from Nicotiana tabacum and 1-and 2-year-old persimmon (D. deyangensis) seedlings cultivated in the orchard at Northwest A&F University under natural conditions. Online analysis of the open reading frame of DdSOC1 was done using the ORF Finder. The physicochemical property of the encoded protein was predicted using Expasy ProtParam program. The MEGA7.0 software was used to create the phylogenetic tree. QRT-PCR was used to examine the expression features of DdSOC1. On the one-deficient and three-deficient plates, the self-toxicity and self-activation of DdSOC1 were explored. Verification of the screening library and yeast interaction was done on a four-lack plate. Confocal microscopy was used in the BiFC experiment. [Results] The findings demonstrated that D. deyangnsis SOC1 shared a close genetic distance with SOC1 from Diospyros lotus, Actinidia chinensis, Actinidia eriantha, Camellia sinensis and other species. Populus alba, Vitis vinifera, Malus domestica, Prunus persica, Mangifera indica and other species were distantly linked to D. deyangnsis SOC1 protein. Furthermore, D. deyangnsis SOC1 protein was the most distantly related to that of the herbaceous plants Triticum aestivum and Oryza sativa. Online analysis demonstrated that DdSOC1 protein encodes 126 amino acids. The molecular weight is 14.56 ku. Its isoelectric point is 5.62. SOC1 expression was the highest during flowering and lowest during the bud stage in annual flowering D. deyangnsis stems. As the flowering process progressed, SOC1 expression in the leaves rose. SOC1 expression in the buds peaked during the seedling stage and decreased during the flowering stage. For Y2H, the first deficient plate had plaques, whereas the third plate had none. It demonstrated that DdSOC1 did not have autotoxicity and autoactivation. Following that, DdSOC1 was employed as the bait protein to test the cDNA library of Fuping persimmon. Following colony PCR, the blue plaque on the four-deficient plate in the sieve library was forwarded for sequencing. By comparing the sequences obtained from the screening library with the NCBI BLAST and the genome annotation of D. deyangnsis, seven putative interacting proteins (MIOX, AGL14, JOINTLESS, GL2, NOVEIN, NBS and UBC7) were screened out. The AD vectors of JOINTLESS, NOVEIN, GL2 and other interacting proteins were introduced into BD-SOC1 yeast-competent cells to verify yeast two-hybrid interactions. PGBKT7-53 + pGADT7-T, pGBKT7-Lam + pGADT7-T, and BD-SOC1 + pGADT7 were used as positive, negative and blank control. The combined plasmid was effectively transferred into yeast strains. The findings demonstrated that nine sets of yeast combinations were able to establish white colonies on DDO plates. Plaque was absent from both negative and blank controls on QDO and QDO/X/A plates. On QDO/X/A plates, the positive control and seven yeast combinations (BD-SOC1+AD-NBS, BD-SOC1+AD-JOINTLESS, BD-SOC1+AD-UBC7, BD-SOC1+AD-MIOX, BD-SOC1+AD-GL2, BD-SOC1+AD-NOVEIN and BD-SOC1+AD-AGL14) could grow properly and turn blue. The SOC1 protein and interaction proteins MIOX, JOINTLESS, AGL14, NOVEIN, UBC7 and GL2 in D. deyangensis were evaluated based on the results of the yeast two-hybrid. The pSPYCE (CE) vector of putative interacting proteins and the pSPYNE (NE) vector of DdSOC1 were constructed. Following co-injection, YFP fluorescence signals were seen in tobacco cells. The findings demonstrated that JOINTLESS-cYFP+SOC1-nYFP produced the strongest yellow fluorescence in the tobacco cell membrane and nucleus out of the seven combinations. Other combinations (NOVEIN-cYFP+SOC1-nYFP, UBC7-cYFP+SOC1-nYFP, NBS-cYFP+SOC1-nYFP, GL2-cYFP+SOC1-nYFP and MIOX-cYFP+SOC1-nYFP) detected yellow fluorescence on the cell membrane, while the combination of AGL14-cYFP+SOC1-nYFP produced yellow fluorescence in the nucleus. According to the aforementioned findings, DdSOC1 interacted with seven potential plant interacting proteins. D. deyangensis seedlings with various characteristics (flowering and non-flowering) were examined for the expression of DdSOC1 and its interaction proteins in young leaves (leaves close to the apical bud) and mature leaves (adult leaves distant from the apical bud). According to the findings, juvenile leaves had higher expression levels of SOC1, AGL14, JOINTLESS, NOVEIN, GL2, UBC7 and NBS than mature leaves, but younger leaves had lower expression levels of MIOX. The expression levels of SOC1, NOVEIN and MIOX in young leaves were lower than those in mature leaves in the two-year-old D. deyangensis seedlings, whereas the other genes (GL2, UBC7, NBS, AGL14 and JOINTLESS) exhibited a contrast pattern. [Conclusion] This study isolated and cloned the DdSOC1 gene, which was relatively conserved in the evolution of woody plants; DdSOC1 integrated flowering signals from leaves to achieve the transition from vegetative growth to reproductive growth; the results from Y2H and BiFC confirmed that DdSOC1 interacted with interaction protein (MIOX, AGL14, JOINTLESS, GL2, NOVEIN, NBS and UBC7); MIOX may play a role in delaying flowering, while AGL14, JOINTLESS, GL2 and NBS may have a positive influence on the short-childhood of D. deyangensis.